(18)F-FP-PEG(2)-β-Glu-RGD(2): A Symmetric Integrin α(v)β(3)-Targeting Radiotracer for Tumor PET Imaging - Hu, Kongzhen (PLoS One, 2015)
Radiolabeled cyclic arginine-glycine-aspartic (RGD) peptides can be used for noninvasive determination of integrin α(v)β(3) expression in tumors. In this study, we performed radiosynthesis and biological evaluation of a new (18)F-labeled RGD homodimeric peptide with one 8-amino-3,6-dioxaoctanoic acid (PEG(2)) linker on the glutamate β-amino group ((18)F-FP-PEG(2)-β-Glu-RGD(2)) as a symmetric PET tracer for tumor imaging. Biodistribution studies showed that radioactivity of (18)F-FP-PEG(2)-β-Glu-RGD(2) was rapidly cleared from blood by predominately renal excretion. MicroPET-CT imaging with (18)F-FP-PEG(2)-β-Glu-RGD(2) revealed high tumor contrast and low background in A549 human lung adenocarcinoma-bearing mouse models, PC-3 prostate cancer-bearing mouse models, and orthotopic transplanted C6 brain glioma models. (18)F-FP-PEG(2)-β-Glu-RGD(2) exhibited good stability in vitro and in vivo. The results suggest that this tracer is a potential PET tracer for tumor imaging.